Nanostructured photocatalysts for nitrogen fixation. (May 2020) - Zhang, Guoqiang; Sewell, Christopher D.; Zhang, Peixin; Mi, Hongwei; Lin, Zhiqun
Abstract: There is a growing interest in designing nanostructured photocatalysts which provide improved photocatalytic activity due to their efficient photogenerated carrier separation and transfer. Compared with their bulk counterparts, nanostructured materials usually possess many more defects and active sites in addition to higher specific surface areas, and as a result, are more able to activate N2 molecules. This review highlights recent advances in the tailoring of nanostructures (1D nano-tubes/belts/wires/rods, 2D nanosheets, 3D assembled hierarchical architectures) in photocatalysts to enhance their N2 fixation properties. First, the advantages of photocatalytic N2 fixation and nanostructured photocatalysts are briefly introduced. Subsequently, several nanostructures designed for N2 photofixation are presented. Finally, the critical challenges and future prospects of this emerging field are discussed. Graphical abstract: Image 1 Highlights: A comprehensive summary of recent advances in nanostructured photocatalysts for nitrogen fixation for the first time . Providing critical insights to understand the correlation between the nanostructures and their catalytic activity. Focusing on the effects of different nanostructures on charge separation and nitrogen activation. Summarizing a few critical issues in photocatalytic synthesis of ammonia for future studies.